Prevalence of occupational accident; and injuries and their associated factors in iron, steel and metal manufacturing industries in Addis Ababa. Issue 1 (1st January 2020) - Berhan, Eshetie
Abstract: The purpose of the research is to investigate the prevalence of workplace accident/injuries (policymakers) and the associated factor in Iron, Steel and Metal Manufacturing Industries (ISMMI) in Addis Ababa, Ethiopia. To achieve this objective, primary data using a questionnaire was collected from 446 production workers in 89 ISMMI. The major findings of the study showed that both availability and cultures of Personal Protective Equipment (PPE) usage are found to be lower. The prevalence of workplace AoI in the metal manufacturing industries in Addis Ababa is found to be relatively very high as compared to previous studies. Employees have mostly faced AoI such as fracture, dislocation, abrasion, suffocation, burn and piercing in their workplace. Female workers are more likely to face cut AoI than their male counterparts. Moreover, employees who are working in medium and large size industries have more likely faced exhaustion, dislocation, sprain, fracture, and burn AoI than employees who are working in small size industries. The study concluded that workplace accident in ISMMI in Addis Ababa is very high and mostly caused by the absence of and poor culture on PPE usage that requires awareness creation and interventions from policymakers to improve the working environment.